Economic Returns to Education: What We Know, What We Don't Know, and Where We Are Going Some Brief Pointers - Colm P. Harmon (Institute for the Study of Labor (IZA), 2011)
The estimation of the economic return to education has perhaps been one of the predominant areas of analysis in applied economics for over 50 years. In this short note we consider some of the recent directions taken by the literature, and also some of the blockages faced by both science and policymakers in pushing forward some key issues. This serves by way of introduction to a set of papers for a special issue of the Economics of Education Review.
Keywords: J08; J30; J38; C21; 330; education policy; returns to education; Bildungsertrag; Schätztheorie